Systematic Review on the Status of Sexually Transmitted Infections (STI) in the Philippines: Challenges and Opportunities - Arellano, Millen May; Abalos, Jenette Minelle; Cruz, Jamie Alessandra; Estacio, Danah Marie; Ramasola, Franchesca; Reyes, Ronalaine; Satoya, Angelu; Milanez, Giovanni De Jesus (Asian Journal of Biological and Life Sciences)
Sexually transmitted infections are considered a major global concern not only on a health perspective but more importantly for both the socio and economic status of a country. Articles covering the prevalence of sexually transmitted infections in the Republic of the Philippines were included in this study. The literature search was performed by searching the PubMed and Google Scholar databases. The search term combination of sexually transmitted infections (STI) + Philippines and specific keywords for STI + Philippines were used. Specific STI keywords consisted of chlamydia, Neisseria, syphilis, HIV/AIDS, Hepatitis B (HBV), Herpes simplex virus (HSV), and Human papilloma virus (HPV). A second round of search was done using keywords gonorrhea, Treponema pallidum, and genital warts. To this date, sexually transmitted infections, regardless of its etiology, are considered censored points of discussion in many developing countries. The reason may be attributed to the several psychological stigmas attached to it. For this reason alone, studies directed to STIs have been a challenge to several researchers due to the unavailability of respondents. In this study, we have provided the current status and opportunities of STI surveillance studies in the Republic of the Philippines.
Keywords: Female sex workers; Male sex workers; Philippines; prevalence; Sexually transmitted infection